A combined mechanism (the open pores-cake dissolution) model for describing the trans-membrane pressure (Pb(t)) reduction in the backwash process at a constant flow rate. Issue 6 (December 2021) - Gao, Shujuan; Wang, Zhan; Ren, Tao; Zhang, Yonghe
Abstract: Accurate prediction of the trans-membrane pressure ( P b ( t )) reduction in the backwash process at a constant flow rate has a great significance for the industrial backwash process. In this paper, a combined mechanism (the open pores-cake dissolution) model was established to predict the variation of P b ( t ) in the backwash process at a constant flow rate for 0.1 µm polyacrylonitrile (PAN) membrane fouled with activated sludge suspension. Meanwhile, the proposed model was validated by using other foulants (yeast, bovine serum albumin and sodium alginate), membranes (0.1 µm polyethersulfone (PES) and polyvinylidene fluoride (PVDF) membranes) and at different fouling conditions (filtrate flow rate, mixed liquor suspended solid (MLSS) concentration and cross-flow velocity). The results showed that the model predictions were in good agreements with experimental data ( R 2 >0.986, relative error σ ¯ <3.28%). Moreover, according to the variation of P b ( t ), the backwash process can be divided into three stages: (i) P b ( t ) decreased rapidly ( t he open pores-cake dissolution) before t i (the first transi t i on point); (ii) P b ( t ) decreased slowly (cake dissolution) in the range of t i to t j (the second t ransi t ion point); (iii) P b ( t ) is almost constan t (without the open pores and cake dissolution) after t j . Thus, the proposed model would provide a theoretical basis for achieving the goal of high-efficient and energy-saving in the backwash process at a constant flow rate. Graphical Abstract: ga1 Highlights: A model was established for constant flow rate backwash process. P b ( t ) reduction can be divide into sharply/ slowly decreasing stage and steady stage. Transition points and time of the backwash mechanism was determined. The variation of the available membrane area ratio ( A b ( t )/ A m ) was analyzed.